COMPARATIVE EFFECTS OF TASK-ORIENTED PROGRAM AND PROPRIOCEPTIVE TRAINING ON BALANCE, GAIT AND QUALITY OF LIFE IN PATIENTS WITH HEMIPLEGIC STROKE - MAQBOOL, S; KAMRAN, S; NAZ, S; AMJAD, A; MAQBOOL, T (Biological and Clinical Sciences Research Journal, 2024)
This study compared the effectiveness of a Task-Oriented Program and Proprioceptive Training in improving balance, gait, and quality of life in a specific population. Objective: The objective of this study was to evaluate and compare the outcomes of the Task-Oriented Program and Proprioceptive Training on participants' balance, gait, and quality of life. Methods: The study included two treatment groups: Group A (Task-Oriented Program) and Group B (Proprioceptive Training). The gender distribution and frequencies were assessed within each group. Various variables were measured at different time points, and tests for normality were conducted. Independent samples t-tests were performed to analyze the differences in mean scores between the two groups. Results: In Group A, comprising 36 participants, there were 17 males (47.2%) and 19 females (52.8%), while Group B, also with 36 participants, consisted of 16 males (44.4%) and 20 females (55.6%). At baseline, no significant difference was observed in mean Berg Balance Scale (BBS) scores between the two groups. However, after four weeks of intervention, Group A demonstrated significantly higher BBS scores than Group B (mean difference = 6.26, p < 0.001). This trend continued at week 8, with Group A showing a substantial advantage (mean difference = 14.56, p < 0.001). Regarding Motor Assessment Scale (MAS) scores, similar patterns emerged. At baseline, no significant difference was found. Still, after four weeks, Group A had significantly higher MAS scores than Group B (mean difference = 7.21, p < 0.001), which further increased at week 8 (mean difference = 13.88, p < 0.001). Conclusion: The Task-Oriented Program yielded superior outcomes compared to Proprioceptive Training in improving participants' balance, gait, and quality of life, as indicated by significantly higher BBS and MAS scores. These findings highlight the effectiveness of the Task-Oriented Program as an intervention for enhancing balance and motor performance in the specific population studied.